2010
DOI: 10.1111/j.1365-2133.2010.09807.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute hair loss on the limbs in frontal fibrosing alopecia: a clinicopathological study of two cases

Abstract: References1 Gazerani P, Pedersen NS, Drewes AM, Arendt-Nielsen L. Botulinum toxin type A reduces histamine-induced itch and vasomotor responses in human skin. Br J Dermatol 2009; 161:737-45. 2 Wallengren J. Neuroanatomy and neurophysiology of itch. Dermatol Ther 2005; 18:292-303. 3 Koshi EB, Short CA. Placebo theory and its implications for research and clinical practice: a review of the recent literature. Pain Pract 2007; 7:4-20. 4 Weinfeld PK. Successful treatment of notalgia paresthetica with botulinum toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 9 publications
3
30
0
2
Order By: Relevance
“…To date, FP have been described as a sign of lichenoid inflammation of facial vellus hair follicles [1,2,3]. Histologic features presented herein, in association with the previously described good response to oral isotretinoin, suggest that prominent sebaceous lobules with dilated ducts associated with an abnormal elastic framework are the main explanation for the formation of FP in the context of FFA.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…To date, FP have been described as a sign of lichenoid inflammation of facial vellus hair follicles [1,2,3]. Histologic features presented herein, in association with the previously described good response to oral isotretinoin, suggest that prominent sebaceous lobules with dilated ducts associated with an abnormal elastic framework are the main explanation for the formation of FP in the context of FFA.…”
Section: Discussionmentioning
confidence: 57%
“…Since then, several features have been associated with FFA, such as glabellar red dots [2], body hair involvement [3], lichen planus pigmentosus (LPPigm) [4], depression of the frontal veins [5], and facial papules (FP) [6]. The disease is now regarded by many authors as a generalized skin condition [7].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, hair loss of the eyebrows, eyelashes, trunk, upper and lower extremities [1], moustache and beard area, and sideburns can also occur [2,3,4]. Exclusive involvement of the sideburns in FFA was reported by us in a single case; however, it may be more prevalent [2].…”
Section: Introductionmentioning
confidence: 76%
“…Classical diffuse LPP somewhere else on the scalp has been stated in organization with FFA in one sixteenth percent [2,3,9,15]. Whereas scalp LPP is especially a complaint of terminal pigmented hairs, it's been suggested that in FFA, vellus and intermediate hairs square measure affected preferentially, [8,19] though this has not been confirmed in an added gain information of [7] ironically, most terminal pigmented hairs on the scalp square measure unaffected in FFA, with handiest these on the hairline involved. Symptoms also will be less frequent in FFA [3,9,19] (3-55%) than in LPP (60-70%) [18].…”
Section: Introductionmentioning
confidence: 96%
“…As good as eyebrows, eyelashes could also be lost [2,3] and involvement of facial vellus hairs will overtimes end in tiny flesh colored facial papules [4][5][6]. Limb and flexural hair are on the whole affected, more commonly without a related signs or rash [7,8]. The condition now not solely influences postmenopausal females as a small however growing number of instances had been suggested in premenopausal females and in guys [9].…”
Section: Introductionmentioning
confidence: 99%